2018
DOI: 10.1002/anie.201802509
|View full text |Cite
|
Sign up to set email alerts
|

Localizing Antifungal Drugs to the Correct Organelle Can Markedly Enhance their Efficacy

Abstract: A critical aspect of drug design is optimal target inhibition by specifically delivering the drug molecule not only to the target tissue or cell but also to its therapeutically active site within the cell. This study demonstrates, as a proof of principle, that drug efficacy can be increased considerably by a structural modification that targets it to the relevant organelle. Specifically, by varying the fluorescent dye segment an antifungal azole was directed from the fungal cell mitochondria to the endoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…The incidence of fungal infections has risen sharply in recent decades and the prevention and treatment of these infections relies on a very limited number of classes of antifungal drugs . Therefore, in recent years, several research groups, including ours, have been engaged in the study and development of membrane‐disrupting antifungal cationic amphiphiles based on the pseudo‐oligosaccharide structures of aminoglycoside (AG) antibiotics .…”
Section: Figurementioning
confidence: 99%
“…The incidence of fungal infections has risen sharply in recent decades and the prevention and treatment of these infections relies on a very limited number of classes of antifungal drugs . Therefore, in recent years, several research groups, including ours, have been engaged in the study and development of membrane‐disrupting antifungal cationic amphiphiles based on the pseudo‐oligosaccharide structures of aminoglycoside (AG) antibiotics .…”
Section: Figurementioning
confidence: 99%
“…[7][8][9] Thei ncidence of fungal infections has risen sharply in recent decades and the prevention and treatment of these infections relies on av ery limited number of classes of antifungal drugs. [10][11][12] Therefore,i nr ecent years,s everal research groups,i ncluding ours,h ave been engaged in the study and development of membrane-disrupting antifungal cationic amphiphiles based on the pseudo-oligosaccharide structures of aminoglycoside (AG) antibiotics. [13][14][15][16][17][18] The design of these antifungal agents is based on the attachment of hydrophobic residues to one or more positions of the AG scaffold.…”
mentioning
confidence: 99%
“…[76] Themore hydrophilic naphthalimide-derived probes localized to lysosomes,a nd the more hydrophobic naphthalimide derivatives localized to the ER with high selectivity.W er ecently demonstrated that implementing the organelle-targeting approach can improve the performance of azole antifungal drugs. [77] Members of the azole class of antifungal drugs are the first-line treatment for invasive fungal infections. [78][79][80] Despite three decades of broad clinical use,fundamental questions about the uptake and localization of antifungal azoles within fungal cells had remained unanswered.…”
Section: Targeting the Endoplasmic Reticulum And Golgi Apparatusmentioning
confidence: 99%